The Significance of Dysthymia Symptoms in Colleen Hoover’s Regretting You - Smarandreetha, Falsyawal Galang; Pasopati, Rommel Utungga (CV. Tripe Konsultan, 2024)
Colleen Hoover's novel entitled Regretting You was first published in 2019. The novel reflects the intricate layers of human relationships of self-discovery, forgiveness, and lifelong family connections. Morgan and her teenage daughter, Clara, is dealing with the tragic deaths of Morgan's husband and Clara's father. As they deal with their grief and try to rebuild their lives, secrets and misunderstandings emerge, straining their relationship and causing them to experience dysthymia. Dysthymia is a lifelong form of depression, according to Michael E. Thase and Susan S. Lang. Then, how the symptoms of dysthymia depicted by Morgan and Clara in Colleen Hoover’s Regretting You? Employing a qualitative research approach, the researchers explore the symptoms of dysthymia, including changes in feeling, thinking, and behavior. Morgan and Clara's dysthymia evolves as they navigate the conflicts in the story, mainly due to the grief resulting from their loss. As a result, their mental and emotional health suffers greatly. This leads to the conclusion that their dysthymia exacerbates the tension in their mother-daughter relationship, making it difficult for them to communicate effectively and solve problems, all due to their enduring mild depression.